Distinguishing Semantic Preference Of Hurry And Rush Via Collocational Patterns: A Corpus-Based Study - I Made Luis Harta; Gede Primahadi Wijaya Rajeg; Ni Ketut Sri Rahayuni (FKIP, Universitas Palangka Raya, 2023)
Verbs are the action words that describe what the subject is doing. Many verbs are synonymous, namely, they could convey very similar meanings, such as the verbs hurry and rush, which roughly convey ‘speeded actions’. This paper presents a corpus linguistic study of the semantic preferences of hurry and rush in terms of the nouns that co-occur (i.e., collocate) with them. The noun collocations data, and their degree of association with the verbs, were extracted from the Corpus of Contemporary American English focusing on collocates appearing within a two-words window to the right (i.e., after) and to the left of (i.e., before) hurry and rush. These collocates were further analyzed semantically for (i) their semantic fields using the Concepticon catalogue (List et al. 2023) and (ii) their broader noun types (Wren 2021). Overall, we found that hurry and rush exhibit distinct collocational patterns and semantic preferences, particularly in terms of the preferred semantic fields (e.g., KINSHIP, RELIGION AND BELIEF, EMOTION AND VALUE are semantic fields preferred for the left-side collocates of hurry while rush is associated with THE BODY and SOCIAL AND POLITICAL RELATIONS). This study shows that synonymous verbs can have distinct semantic patterns.